La modalité appréciative : vers une sémantique de good - Viviane Arigne (Anglophonia)
This article analyses the lexical semantics of the adjective good in indefinite singular NPs such as a good wife, a good burglar or good bread. The adjective good is central to the semantic concept of evaluative modality defined in the framework of the opposition good vs. bad, which is consensually considered to be a positive vs. negative opposition within which good is seen as the positive term. The study shows that good marks the ontological completeness of an entity construed as an integrated whole, whether the noun referring to this entity is a discrete noun or a mass noun. Good also posits the existence of this integrated whole and its parts, which accounts for it being interpreted as positive. The ontological study is extended to adjectives which, like good, are found in superordinate clauses in the context of meditative-polemic should. Adjectives such as essential, vital, adequate and appropriate, which are often analysed as mandative, treat the propositional content of the subordinate clause as a part of a good integrated whole and can therefore be interpreted as pertaining to the class of evaluative adjectives.